You are on page 1of 16

I-1

(e)
=

(a)
=

100%

II.
(a)
=

100%

(b)
=

(b)
=

100%

(c)
=

III.

(a) =

(d) = 100%
(e) = +

(b)
=

100%

(f) = -

(c) = %


I.
(a) x r%

(d) = (1 %)
IV.
r

= x 1 + r% = x(1 + 100 )

P R%
n A

(b) x y
=

yx
x

(a)

100%

I = P R% n =

PRn
100

(c) x r%
r

= x 1 r% = x(1 100 )
(d) x y
=

xy
x

100%

A=P+I
PRn

= P + 100
Rn

= P(1 + 100 )

I-2

(b)

(b)
n

A= P(1 + R%)
I = A P

= 2rh
= 2rh + 2r 2
= r 2 h

= P(1 + R%) P
V.
(a) P R%
n
= P(1 + R%)n

(c)

(b) P R%
n
= P(1 R%)n
= +
V.

1
3

Ah

(d)
= rl

( = 5%)

= rl + r 2

I.

1
3

r 2 h

(e)
= 4r 2
=
(a) l = 2r

4
3

r 3

360

(b) A = r 2

III.
(a) X Y

360

II.
(a)

(b) C D

= + 2
= Ah

I-3

IV.
ABC
ACD

=b

I
I.

a + b + c = 180()

I.

6
a + b + c + d + e = 360()

II.

13

a = b, p = q ()
4

2
6

7
3

a = b (, AB//CD)
c = b (, AB//CD)
b + d = 180 (, AB//CD)

I-4

AB//CD
(i) a = b ()
ii c = b ()

iii b + d = 180 ()

III.

II.
ABC~XYZ
(i) A = X,B = Y,C = Z;
()
a + b + c = 180

(ii)

AB
XY

BC
YZ

CA
ZX

()

d = a + b

A = X, B = Y, C = Z,
ABC~XYZ(A. A. A. )

AB

BC

XY = YZ =

CA
ZX

ABC~XYZ()

I-5

AB

XY =

CA
ZX

A = X

A = X,C = Z, AB = XY,
ABC XYZ (AAS)

ABC~XYZ()
IV.

AB = XY, BC = YZ, A = X= 90,


ABC XYZ (RHS)
ABC XYZ
(i) A = X,B = Y,C = Z;
()

V.

(ii) AB = XY, BC = YZ, CA = ZX.


()

ABCD
AB = XY, BC = YZ, CA = ZX,
ABC XYZ (SSS)

(a) AB = DC, AD=BC


()
(b) BAD=BCD, ABC=ADC
()
(c) AO = OC, BO = OD
()

AB = XY, BC = YZ, B = Y,
ABC XYZ (SAS)

AB = DC, AD=BC
A = X,B = Y, AB = XY,
ABC XYZ (ASA)

ABCD
()

I-6

BAD=BCD, ABC=ADC ,
ABCD
()

c 2 = a2 + b2
ACB = 90()
VII.

AO = OC, BO = OD,
ABCD
()
AH=HB AK=KC
HK =

1
2

BC HK//BC()

AB = DC, AB//DC ,
ABCD
()
VI.
AB//CD//EF AC=CE
BD=DF ()

ACB = 90
c 2 = a2 + b2 ()
HK//BC AH=HB
AK=KC ()

I-7

VIII.


I.
2 + bx + c = 0 a 0
=

a+b>c, b+c>a, c+a>b


VIII.

2 4
2

II.
= 2 4
2 + bx + c = 0 a 0
(a) > 0
(b) = 0
(c) < 0
III.

()

+ = a

= a

x 2 + x + = 0


I.


I.
a b
ab = a b

(a)

(b)

a
b

II.
i = 1 a b
(a) a i = i a = ai
(b) ai + bi = (a + b)i
(c) ai bi = (a b)i
(d) ai bi = ab
(e)

ai
bi

=b

II.
f x mx n f

III.
(a)f

= 0mx nf x

(b) mx nf x
f

= 0

I-8

I.
m n a, b 0


I.
y x y=kx k

II.

y x y = x k

III.
(a) z x y z=kxy
k
(b) z x y
z=

IV.
(a) z x
m n m>0

z = k1 + k 2 xk1 k 2

(b) z x y
z = k1 x +

k2
y

k1 k 2

II.
M N ,a > 0, a 1 k


(a) a>b b>c a>c
(b) a>b a+c>b+c
(c) a>b
(i)c>0 ac>bc;
(i)c<0 ac<bc
1

(d) a>b>0a < b


(e) a 0a2 > 0

I-9

I
(a) A(x1 , y1 ) B(x2 , y2 )

(h)
(i)

(ii) (iii)

(b) A(x1 , y1 ) B(x2 , y2 )

(c) A(x1 , y1 ) B(x2 , y2 )

y-

I
I.
AB

(a)

(d) m1 , m2 l1 , l2
(i) l1 //l2 m1 = m2
(ii) l1 l2 m1 m2 = 1
ONAB AN=NB
(e) l (x1 , y1 )(x2 , y2 )
m
(i) : l

()
(b)

(ii) : l

(f) Ax+By+C=0

AN=NB ONAB

y=mx+c
m c y-
x- y=0
y- x=0

()
(c)

(g)

AC:CB = m:n

CNAB AN=NB
CN O
()

I-10

(d)

(c)

AB=CD OM=ON

APB = 90 AB
()

()
(d)
(e)

OM=ON AB=CD

x=y
()

a=b

()
III.
II.

(a)

(a)

x=2y ()

(i) x=yAB = CD()


(ii) AB = CD x=y()

(b)
(b)

AB APB = 90
()

(i) x=yAB = CD()


(ii) AB = CD x=y()

I-11

(c)

(b)

(i) AB = CD
AB = CD()
(ii) AB = CD
AB = CD()

x=y ()
(c)

(d)

AB: CD=m:n
()

x=y A,B,C D
()
(d)

(e)

AB: CD=x:y
()

A+C = 180
B+D = 180
A,B,C D
()

IV.
(a)

(e)

y=x
A+C = 180
B+D = 180
()

A,B,C D
(=)

I-12

V.

(d)

(a)

PQ T
PQ T
PQOT()
()
(b)
(e)

PQOT
PQ T()
(c)

=
=
PTQ T
()
I
I.
(a)

PA A PB B
(i) PA = PB
(ii) x = y
(iii) m = n ()

I-13

(b) (0 < < 360)

r =

IV.

x2 + y2

II.

III.

I-14

II

f(x)+k

(k>0)

f(x)-k

(k>0)

f(x+k)

(k>0)

f(x-k)

(k>0)

kf(x)

(k>1)

y-
k

kf(x)

(0<k<1)

y-
k

f(kx)

(k>1)

x-
1

I.
f(kx)

(0<k<1)

x-
1

II.

III.
(a)

-f(x)

x-

f(-x)

y-

II

(b)

I-15


I.
n!= n(n-1)(n-2) 321
n
II. <>
n r
0 r n
Prn
Prn

n!
(n r )!

P: Position
n
n!

III.
A B

(a) A B
P(A B) = P(A)+P(B)
(b) A B
P(A B) = P(A)+P(B)- P(A B)
(c) AP(A) + P(A) = 1
A A
IV.
(a) A B
P(A B) = P(A) P(B)

III. <>
n r
0 r n

(b) A B
P(A B) = P(A) P(B|A)

Crn
C rn

Prn
n!

r! r!(n r )!

C: Choose

V.
A B
=P(B|A)


I.

I. : a, a+d, a+2d, a+3d,
(a) T(n) = a+(n-1)d
(b) T(n) =

1
2

[T n 1 + T n + 1 ]

II.
n
p1 , p2 , , pn

(c) T(1), T(2), T(3),


kT(1)+c, kT(2) +c, kT(3) +c,

x1 , x2 , , xn

(d) S(n)=T(1)+T(2)+T(3)++T(n)

=x1 p1 + x2 p2 + + xn pn

S(n) =

n
2

a+T n

= 2 2a + n 1 d

I-16

II. : a, a , a , a ,
(a) T(n) = a

(b) T(n) = T n 1 T n + 1
(c) T(1), T(2), T(3),
kT(1), kT(2) , kT(3) ,
(d) S(n)=T(1)+T(2)+T(3)++T(n)

(b)
= (Q3) (Q1)
(e)
(i)

(ii)
(e)
III.
(a)
x x

I.
(a)

(i)

(b)

z =

xx

(ii)

(i) 68%x x +

(b)

(ii) 95%x 2x + 2

(iii) 99.7%x 3
x + 3

II.
(a)
(i)
=
(ii)
=

IV.

+k

X k

+k

X k

X k